Single-sphere single-crystal DNA crystal microsphere and preparation method and application thereof
Patent Information
- Application Number
- CN202611180451.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-08-05
AI Technical Summary
[0012]本发明中,通过DNA晶体原位形成与聚合物后续固化的协同控制,提高DNA晶体的稳定性,解决了现有技术中液滴内DNA晶体在离开液滴模板后难以保持的问题,并实现液滴内DNA单晶的原位形成、聚合物固化锁定及去油洗出后微球实体化,从而获得保持单球单晶结构的独立DNA晶体微球
本发明通过在含有可交联亲水聚合物的双乳液滴内进行梯度渗透压浓缩,使DNA链在受限液滴环境中原位自组装形成DNA晶体,并通过控制外相盐溶液的初始浓缩强度及后续逐级升高过程,较好地协调了DNA晶体的成核、生长与内核液滴脱水收缩过程,从而提高了DNA晶体形成的可控性和结构均一性。
Smart Images

Figure CN122682512B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer microsphere materials technology, specifically to a single-sphere single-crystal DNA crystal microsphere, its preparation method, and its application. Background Technology
[0002] DNA crystals, due to their programmability, self-assembly, and designable structure, have potential applications in nucleic acid material construction, microstructure templates, detection coding, and functional microsphere construction. Compared with disordered nucleic acid aggregates or ordinary nucleic acid embedding systems, DNA crystals have regular microstructures and relatively well-defined spatial structures, making them more suitable as standardized nucleic acid microstructure units, micro-coding units, or precursors for templated functional materials.
[0003] The formation of DNA crystals depends on specific sequence design, ionic strength, buffer system, local concentration conditions, and a confined growth environment. The applicant previously proposed a technical solution for incubating DNA crystals in a dual-emulsion droplet (publication number CN119980475A). This solution utilizes the dual-emulsion droplet as a confined microreactor, and by controlling parameters such as DNA concentration, droplet size, and external phase osmotic pressure, it achieves controllable nucleation and growth of DNA crystals within the droplet, solving the problem of uneven crystal quantity, size, and morphology in conventional bulk systems. However, this technology mainly addresses the controllable preparation of DNA crystals within the droplet. The resulting DNA crystals typically still rely on the high-salt, confined, and oil-water interface environment within the droplet to maintain their morphology. Once the droplet structure is disrupted, or the crystals undergo processes such as degreasing, washing, transfer to a normal aqueous phase, or redispersing, the original ionic and confined environments are altered, leading to phenomena such as blurred boundaries, local dissolution, breakage, aggregation, and even loss of crystal signal. Therefore, the formation of uniform DNA crystals within droplets is not equivalent to obtaining separable, washable, and independently usable DNA crystal materials, which limits their further use in coding recognition, functional modification, storage and transportation, and product applications.
[0004] To improve the stability of nucleic acid materials, existing technologies typically employ carrier encapsulation or delivery systems to protect nucleic acid molecules. For example, US Patent No. 9339465B2 discloses nucleic acid microspheres and their preparation and delivery methods, which can construct microsphere carriers from nucleic acid molecules such as DNA, RNA, siRNA, mRNA, tRNA, or oligonucleotides; Chinese Patent No. CN111094589A discloses the encapsulation of long DNA using hydrogel beads for subsequent sequencing operations; and Chinese Patent No. CN109851711B discloses soluble hydrogel microspheres and their application in single-cell detection. These technologies demonstrate that carrier encapsulation, hydrogel matrix protection, and formulation treatment are important directions for improving the stability of nucleic acid materials.
[0005] However, the aforementioned nucleic acid stabilization technologies primarily target free DNA, RNA, or other nucleic acid molecules, focusing on the preservation, delivery, or detection of these molecules. They do not address DNA crystals, which possess a regular spatial arrangement. DNA crystals differ from ordinary nucleic acid molecules; their functional properties derive not only from the DNA sequence itself but also from the ordered lattice structure, spatial arrangement, and crystal morphology formed between DNA strands. Therefore, stabilizing DNA crystals requires addressing not only the issue of nucleic acid degradation but also the preservation of crystal structure and morphology, as well as their stability after removal from their native growth environment.
[0006] For crystalline materials, existing technologies include methods to improve crystal stability through cross-linking, immobilization, or formulation. For example, patent document US8558048B2 discloses methods for stabilizing, storing, and formulation protein or nucleic acid crystals. However, such methods are typically designed for the preservation and immobilization of existing crystalline materials and do not address the controllable formation process of DNA single crystals in a confined environment of double emulsion droplets. Furthermore, directly chemically immobilizing or cross-linking DNA crystals may alter DNA interstrand interactions, lattice structure, or subsequent functionalization capabilities, and may not be suitable for maintaining the programmability and structural activity of DNA crystals.
[0007] Therefore, although existing technologies provide strategies for protecting nucleic acid materials and stabilizing crystal materials, neither solves the problem of stabilizing DNA single crystals formed within dual-emulsion droplets after detachment from the droplet template. The formation of DNA crystals within droplets depends on specific ionic environments, buffer systems, and limited growth conditions; during degreasing, washing, transfer, or redispersement processes, problems such as blurred crystal boundaries, structural damage, or crystal loss can easily occur. Existing technologies have not yet provided a solution for fixing a single DNA crystal formed within a droplet within a monodisperse microsphere matrix and maintaining the correspondence between the single sphere and single crystal without damaging the structure and functional properties of the DNA single crystal.
[0008] Furthermore, introducing curable hydrophilic polymers into DNA crystal growth systems is not a simple encapsulation process. Because the presence of hydrophilic polymers alters the viscosity, molecular diffusion behavior, local osmotic pressure response, and the nucleation and crystal growth processes of DNA assembly units within the droplet, there is a mutual influence between the polymer concentration process and the DNA crystal formation process. On the one hand, concentration conditions suitable for DNA crystal formation may not simultaneously meet the requirements for polymer network formation and microsphere solidification; on the other hand, using conditions suitable for rapid polymer concentration may lead to rapid enrichment of DNA assembly units, triggering abnormal nucleation and resulting in phenomena such as fragmented crystals, polycrystalline structures, or crystal agglomeration. Moreover, if the timing or conditions for curing are inappropriate, even if DNA crystals have formed inside the droplet, it is difficult to maintain the integrity of the crystal structure and the microsphere solid during degreasing, cleaning, and transfer.
[0009] Therefore, a new technical approach is still needed in this field to transform DNA single crystals formed within droplets into independently operable physical materials while maintaining the ordered structure and programmable characteristics of DNA crystals, so that they can maintain the single crystal structure and the correspondence between single spheres and single crystals after being removed from the original droplet template environment. Summary of the Invention
[0010] To address the aforementioned technical problems, this invention provides a single-sphere, single-crystal DNA crystal microsphere and its preparation method. The microsphere achieves in-situ formation of DNA crystals and subsequent solidification of the hydrophilic polymer network within the same double emulsion droplet, thereby fixing a single DNA crystal within a single microsphere matrix. This results in DNA crystal microspheres that retain their single-sphere, single-crystal structure even after degreasing, washing, and redispersing.
[0011] A single-sphere, single-crystal DNA crystal microsphere comprises a cross-linked network microsphere matrix formed by curing a cross-linkable hydrophilic polymer, and a DNA crystal located inside and within the cross-linked network microsphere matrix, wherein each microsphere contains only one DNA crystal, forming a single-sphere, single-crystal structure.
[0012] In this invention, the stability of DNA crystals is improved through the synergistic control of in-situ DNA crystal formation and subsequent polymer curing. This solves the problem in existing technologies where DNA crystals within droplets are difficult to maintain after leaving the droplet template. Furthermore, it achieves in-situ formation of DNA single crystals within droplets, polymer curing and locking, and microsphere solidification after degreasing and washing, thereby obtaining independent DNA crystal microspheres that maintain a single-sphere, single-crystal structure. Simultaneously, different DNA crystals can be prepared based on different DNA chains, ensuring that the microsphere matrix retains an observable DNA crystal structure and / or a corresponding fluorescence signal.
[0013] Preferably, the crosslinkable hydrophilic polymer is an anionic hydrophilic polymer containing photocrosslinkable unsaturated groups.
[0014] In this invention, the main function of the polymer is to form a solidified microsphere matrix through photocrosslinking reaction, while simultaneously providing spatial confinement, physical support, and stable protection for the DNA crystals within the droplets.
[0015] More preferably, the anionic hydrophilic polymer is at least one of methacrylamide hyaluronic acid (HAMA), methacrylamide sodium alginate (SAMA), and methacrylamide carboxymethyl cellulose.
[0016] More preferably, the crosslinkable hydrophilic polymer is HAMA or SAMA.
[0017] Both HAMA and SAMA are hydrophilic, anionic, and photocrosslinkable polymers that can be gently cured under 365 nm light conditions without significantly damaging the DNA crystal structure.
[0018] Preferably, the DNA crystal is formed by the self-assembly of DNA chains, wherein the DNA chains are a combination of a central chain (L chain), a side chain (M chain), and a corner chain (S chain), or a self-assembled chain (Z chain).
[0019] In this invention, the DNA strand can be three different DNA strands: a central strand (L strand), a side strand (M strand), and a corner strand (S strand) (the nucleotide sequences of the DNA strands are shown in SEQ ID NO. 1~3 or SEQ ID NO. 6~8). These three different DNA strands constitute a triangular tensioned structural unit. The central strand (L strand) has a triple repeat sequence and is located in the center of the triangular tensioned structural unit. The side strand (M strand) extends in three double helix directions. The corner strand (S strand) is located at the double helix end of the structural unit and pairs with the side strand (M strand). Based on the above-mentioned triangular tensioned structural unit, this invention can periodically assemble and arrange DNA crystals of uniform size through complementary pairing of two base vacancies.
[0020] In this invention, the DNA strand can also be the same self-assembled Z-strand (nucleotide sequence as shown in SEQ ID NO.4 or SEQ ID NO.5), and the two identical self-assembled Z-strands are paired with each other to form a self-assembled structural unit.
[0021] More preferably, the DNA chain is a central chain L chain with the nucleotide sequence SEQ ID NO.1, a side chain M chain with the nucleotide sequence SEQ ID NO.2, and a corner chain S chain with the nucleotide sequence SEQ ID NO.3.
[0022] Preferably, the particle size of the single-sphere single-crystal DNA crystal microspheres is 10~100 μm, and the maximum lateral dimension of the DNA crystal is 1~30 μm. In this invention, the maximum lateral dimension is the longest distance of the DNA crystal projection.
[0023] More preferably, the particle size of the single-sphere single-crystal DNA crystal microsphere is 20~50 μm, and the equivalent diameter or maximum lateral dimension of the DNA crystal is 5~20 μm.
[0024] This invention also provides a method for preparing the above-mentioned single-sphere single-crystal DNA crystal microspheres, comprising the following steps: (1) Prepare an inner aqueous phase solution by mixing DNA strands, crosslinkable hydrophilic polymers, photoinitiators, buffer solutions, surfactants and soluble salts, prepare an intermediate oil phase solution by mixing non-water-soluble substances and non-water-soluble organic solvents, and prepare an outer aqueous phase solution by mixing surfactants. (2) The inner aqueous phase solution, oil phase solution and outer aqueous phase solution obtained in step (1) are respectively introduced into the corresponding channels of the microfluidic chip to prepare a double emulsion droplet loaded with DNA strand; (3) Subsequently, the double emulsion was dropped into an external salt solution with gradually increasing salt concentration for gradient concentration, inducing DNA strands to self-assemble in situ in the internal aqueous environment to form a single DNA crystal. (4) After the DNA crystal is formed, the double emulsion droplets are solidified to form a cross-linked network surrounding the DNA crystal. The oil phase is removed and the microspheres are cleaned to obtain single-crystal DNA crystal microspheres.
[0025] In this invention, uniformly sized W / O / W (water-in-oil) droplets are prepared using a microfluidic chip. During preparation, a low-concentration salt solution containing DNA strands is used as the inner aqueous phase, a non-water-soluble solution as the oil phase, and a buffer solution as the outer aqueous phase. The double-emulsion droplets are gradient-concentrated using salt solutions of varying concentrations. As the salt concentration gradually increases, the concentration difference between the salt solution and the inner aqueous phase causes water molecules to migrate into the salt solution under osmotic pressure, leading to dehydration and concentration of the core droplet. The DNA strand concentration within the double-emulsion droplet gradually increases to the concentration required for DNA crystal growth. This process promotes DNA crystal growth, ultimately resulting in uniformly sized DNA crystals within the double-emulsion droplet, with each droplet containing only a single DNA crystal.
[0026] In this invention, the diameter of the core droplet of the double emulsion droplet obtained in step (2) can be controlled by combining the concentration gradient of the salt solution after gradient concentration, thereby controlling the size range of the DNA crystal obtained, so that the size of the DNA crystal is controllable.
[0027] In this invention, TAE / Mg 2+ The buffer system is composed of tris-hydroxymethylaminomethane (Tris-based), acetic acid, ethylenediaminetetraacetic acid (EDTA), and magnesium ions. Preferably, the ratio is 1×TAE / Mg. 2+ The buffer system comprises 40 mM tris(hydroxymethyl)aminomethane, 20 mM acetic acid, 2 mM ethylenediaminetetraacetic acid and 25 mM magnesium ions; the magnesium ions are preferably provided by magnesium acetate.
[0028] Preferably, in step (1), the surfactant is polyvinyl alcohol.
[0029] Preferably, in step (1), when the DNA chain is a combination of a central L chain, a side M chain, and a corner S chain, the concentration of the central L chain in the aqueous phase solution is 2~20 μM; the central L chain, the side M chain, and the corner S chain are prepared in a concentration ratio of 1:3:3.
[0030] More preferably, the concentration of the central chain L chain is 5~12 μM.
[0031] More preferably, the concentration of the central chain L chain is 7~9 μM.
[0032] Preferably, in step (1), the non-water-soluble substance is at least one of silicone oil, mineral oil, and PDMS.
[0033] Preferably, in step (1), the internal aqueous phase solution contains TAE / Mg. 2+ Buffer system, wherein the TAE / Mg content in the internal aqueous phase solution 2+ The concentration of the buffer system is 0.1×~5×; more preferably 0.2×~1×.
[0034] Preferably, in step (2), the microfluidic chip is made of glass, polydimethylsiloxane, or plastic.
[0035] The microfluidic chip used in this invention includes an input channel for the solution and an output channel, and can be used to prepare dual emulsion droplets loaded with DNA strands.
[0036] Preferably, the photoinitiator is 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylphenylacetone, and the curing treatment is curing under 365 nm light for 10-30 min.
[0037] Preferably, in step (3), the gradient concentration involves placing the two emulsion droplets sequentially into two or more external phase salt solutions with gradually increasing salt concentrations, causing the core droplets of the two emulsion droplets to gradually dehydrate and shrink until the diameter of the core droplets of the two emulsion droplets shrinks to 10~80 μm, and DNA crystals are formed within the droplets.
[0038] More preferably, the gradient concentration includes a first-stage concentration, wherein the concentration of the external phase salt solution used in the first-stage concentration is equal to the TAE / Mg concentration in the internal aqueous phase solution. 2+ The concentration of the buffer system is 5 to 30 times that of the buffer system.
[0039] More preferably, after the first stage of concentration, gradient concentration is further carried out using an external phase salt solution with progressively increasing concentration, and the final concentration of the external phase salt solution is equal to the TAE / Mg concentration in the internal aqueous phase solution. 2+ 70 to 90 times the concentration of the buffer system.
[0040] More preferably, the concentration concentration is achieved by sequentially dropping the dual emulsions into an aqueous solution containing TAE / Mg at a concentration of [missing value]. 2+ The buffer system is concentrated in an external phase salt solution with concentrations of 20, 40, 60, and 80 times; preferably, the time interval between two adjacent liquid changes is 1 day.
[0041] Preferably, in step (2), before gradient concentration, the core droplet diameter of the initial dual emulsion droplet is 80~300 μm, and the core droplet diameter of the dual emulsion droplet after gradient concentration is 10~80 μm.
[0042] More preferably, the core droplet diameter of the initial dual emulsion droplet is 120~200 μm, and the core droplet diameter of the gradient-concentrated dual emulsion droplet is 20~50 μm.
[0043] Preferably, in step (4), the specific steps for removing the oil phase and cleaning are as follows: after the solidification treatment, the oil phase is removed by filtration and then cleaned with a salt solution, wherein the salt solution is a 2 M NaCl aqueous solution.
[0044] In this invention, the curing process allows crosslinkable hydrophilic polymers to form a continuous or semi-continuous crosslinked network around the DNA crystal. Through polymer confinement and post-curing, the single crystals formed within the droplet retain their independent microsphere structure after degreasing and washing, which is beneficial for obtaining microsphere entities with clear boundaries and complete morphology. Compared with DNA crystals within droplets that are not cured or without polymer protection, this microsphere matrix can reduce the risk of morphological damage, crystal loss, or structural obfuscation during degreasing, washing, transfer, or storage, and helps improve the storage stability of DNA crystals.
[0045] This invention also provides the application of the above-mentioned single-sphere single-crystal DNA crystal microspheres in the preparation of carriers for nucleic acid coding, molecular tagging, or information storage.
[0046] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention utilizes gradient osmotic pressure concentration within a dual emulsion droplet containing a crosslinkable hydrophilic polymer to enable DNA chains to self-assemble in situ into DNA crystals within a confined droplet environment. By controlling the initial concentration intensity of the outer phase salt solution and the subsequent gradual increase in concentration, the nucleation, growth, and dehydration shrinkage processes of the DNA crystals are effectively coordinated, thereby improving the controllability and structural uniformity of DNA crystal formation.
[0047] This invention further solidifies a crosslinkable hydrophilic polymer after DNA crystal formation, forming a crosslinked network microsphere matrix, thereby spatially fixing and structurally protecting the DNA crystal formed within the droplet. This reduces problems such as boundary blurring, structural damage, crystal loss, or aggregation that occur during degreasing, washing, transfer, and redispersing of DNA crystals, improving the structural stability and independent operability of the DNA crystal after detachment from the droplet template.
[0048] This invention realizes an integrated preparation process of in-situ DNA crystal formation, subsequent polymer solidification and locking, and microsphere solidification after degreasing and washing. It can obtain single-sphere single-crystal DNA crystal microspheres that encapsulate a single DNA crystal inside a single microsphere. It has the characteristics of microsphere monodispersity, controllable DNA crystal structure, and microsphere solid stability, and can be used in nucleic acid coding, molecular tag labeling, or information storage carrier applications. Attached Figure Description
[0049] Figure 1 This is a diagram showing the initial state of the double emulsion droplets prepared in Example 1.
[0050] Figure 2 This is a diagram showing the state of the biemulsion droplets and crystals during the gradient concentration process in Example 1.
[0051] Figure 3 This is a bright-field microscope image of the single-sphere, single-crystal DNA crystal microspheres prepared in Example 1.
[0052] Figure 4 The images shown are SEM images of the single-sphere, single-crystal DNA crystal microspheres prepared in Example 1, where a and b are SEM images at scales of 200 μm and 10 μm, respectively.
[0053] Figure 5 These are microscope images of the double emulsion droplets prepared in Example 2 under bright field and fluorescence.
[0054] Figure 6These are microscope images of the single-sphere, single-crystal DNA microspheres prepared in Example 2 under bright field and fluorescence conditions.
[0055] Figure 7 This is a SEM image of the single-sphere, single-crystal DNA crystal microspheres prepared in Example 3.
[0056] Figure 8 The images shown are fluorescence micrographs of the single-sphere single-crystal microspheres prepared in Examples 4 to 6, where A to C are images from Examples 4 to 6, respectively.
[0057] Figure 9 Images of DNA crystals in the double emulsion droplets of Example 1 and Comparative Example 1 are shown, where a and b are images corresponding to Example 1 and Comparative Example 1, respectively.
[0058] Figure 10 This is the image of Comparative Example 2 before it was cured.
[0059] Figure 11 The image shows the microspheres obtained after direct one-step concentration in Comparative Example 3.
[0060] Figure 12 Images of single-sphere DNA crystal microspheres containing Alexa Fluor 488 labeled DNA crystals prepared in Example 2 after being stored for 20 days under different humidity and temperature conditions. Detailed Implementation
[0061] The present invention will be further described in detail below with reference to the embodiments, but the implementation of the present invention is not limited to the following embodiments.
[0062] All raw materials used in this invention are commercially available. In the specific embodiments of this invention, the DNA strands used were synthesized by Sangon Biotech (Shanghai) Co., Ltd. Preparation of TAE buffer stock solution (50×TAE buffer): Add 242 g (2 mol) of Tris base and 37.2 g (0.1 mol) of EDTA to 800 mL of deionized water, stir until fully dissolved, add 57.1 mL of acetic acid, and then add deionized water to a final volume of 1 L. 50×TAE / Mg 2+ Preparation of buffer solution: Dissolve 26.806 g magnesium acetate tetrahydrate in 80 mL of 50×TAE buffer, and then bring the volume up to 100 mL with 50×TAE buffer.
[0063] Example 1 Central chain L chain: ACACCGTACACCGTACACCGT (SEQ ID NO.1); Edge chain M chain: GAGCAGCCTGTACGGACATCA (SEQ ID NO.2); Angular chain S chain: TCTGATGTGGCTGC (SEQ ID NO.3).
[0064] (1) 50×TAE / Mg 2+ The buffer solution was diluted with deionized water to a concentration of 0.2 × TAE / Mg. 2+ With 0.2×TAE / Mg 2+ As a solvent, 0.5% (w / v) HAMA, 0.05% (w / v) 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylphenylacetone and 0.2% (w / v) polyvinyl alcohol (PVA) solution were added and mixed to obtain the inner aqueous phase solvent. Three DNA strands (central strand L, side strand M, and corner strand S) were mixed in a molar ratio of 1:3:3 and added to the inner aqueous phase solvent, ensuring the concentration of the central strand L was 8 μM. This mixture was then transferred to a PCR apparatus and annealed from 95°C to 20°C at a rate of 0.6 °C / min to obtain the inner aqueous phase solution. An oil phase solution was obtained by mixing dimethyl silicone oil with a viscosity of 50 cst and polydimethylsiloxane (PDMS) in a ratio of 8:2; the external aqueous phase solution was an aqueous solution containing 2.5 wt% PVA.
[0065] (2) The inner aqueous phase solution and the intermediate oil phase solution from step (1) are respectively introduced into the corresponding channels of the glass capillary microfluidic chip. The flow rates of the inner aqueous phase solution, the intermediate oil phase solution, and the outer aqueous phase are adjusted to 2000 μL / h, 3000 μL / h, and 28000 μL / h, respectively, to construct W / O / W dual emulsion droplets, such as... Figure 1 As shown, the core droplet diameter is approximately 150 μm. Subsequently, the dual emulsion droplets were subjected to gradient concentration in salt solutions of varying concentrations, wherein the salt solutions used were the same TAE / Mg ratio as the inner aqueous phase. 2+ In this system, the salt concentration of the salt solution relative to the salt concentration of the inner aqueous phase solution is 20, 40, 60, and 80 times respectively, with each solution change occurring every one day. Figure 2 As shown, after concentration, the diameter of the core droplet of the dual emulsion droplet is reduced to about 35 μm, and a single DNA crystal is formed inside the droplet with a crystal size of about 12 μm.
[0066] (3) The double emulsion was dropped and cured under 365 nm light for 20 minutes. After curing, the sample was placed at 20°C and allowed to stand for 12 h. Then, oil removal was performed by vacuum filtration, followed by washing with 2M NaCl aqueous solution. The cleaned DNA-containing microspheres were observed under a microscope. The results are as follows: Figure 3 As shown, the obtained microspheres have a diameter of approximately 28–30 μm and exhibit good monodispersity. The obtained microspheres were freeze-dried, and their morphology was observed using scanning electron microscopy (SEM). The results are as follows: Figure 4 As shown, the low-magnification SEM image reveals that the obtained microspheres have a relatively regular overall morphology, a relatively concentrated particle size distribution, and good monodispersity. In the high-magnification image, angular structures can be observed inside the microspheres. Combining the microscopic observation and SEM results, it can be concluded that under the conditions of this experiment, the DNA crystals formed within the droplets can be transformed into microsphere entities after polymer solidification and remain inside the microspheres.
[0067] Example 2 The preparation method is the same as in Example 1, except that the central chain L chain is replaced with the central chain L chain modified by Alexa Fluor 488 (modified by Sangon Biotech (Shanghai) Co., Ltd.), and its amino acid sequence is 5'-Alexa Fluor488-ACACCGTACACCGTACACCGT-3'. First, a central L-chain modified with a 5'-terminal amino group is synthesized or provided, and dissolved in carbonate buffer or other weakly alkaline buffer suitable for NHS ester reactions. Then, Alexa Fluor 488 NHS ester is added, and the reaction is carried out under light-protected conditions, allowing Alexa Fluor 488 to be grafted to the 5' end of the central L-chain via an amide bond. After the reaction, the free fluorescent dye is removed by purification using a desalting column, ultrafiltration, HPLC, or PAGE to obtain the Alexa Fluor 488-modified central L-chain.
[0068] After gradient concentration was completed, the resulting double emulsion droplets were observed using an inverted fluorescence microscope. The results are as follows: Figure 5 As shown, the crystals within the droplet can be identified under both bright-field and fluorescence channels, demonstrating that fluorescent labeling can be used to visually characterize the crystals formed within the droplet. Under the conditions of this embodiment, the crystals within the droplet exhibit a clear signal under the fluorescence channel, corresponding to the crystal positions observed under bright-field conditions.
[0069] The cleaned microspheres were observed using an inverted fluorescence microscope. The results are as follows: Figure 6 As shown, a crystal signal can be observed under the fluorescence channel, and the corresponding microsphere outline can be observed under bright field. The two exhibit a good spatial co-localization relationship, which can be used to help explain that the fluorescently labeled crystal is located inside the microsphere. Under the conditions of this embodiment, the complete fluorescent crystal signal can still be observed after washing and rinsing.
[0070] Example 3 The preparation method is the same as in Example 1, except that HAMA is replaced with sodium methacrylamide (SAMA) of the same concentration.
[0071] like Figure 7As shown in the figure, SEM observation reveals that the obtained microspheres exist as independent microspheres, and the corresponding DNA crystal structure can be observed inside the microspheres. This example illustrates that, in addition to HAMA, SAMA can also be used as a crosslinkable hydrophilic polymer matrix for constructing single-sphere, single-crystal DNA crystal microspheres.
[0072] Example 4 The preparation method is the same as in Example 2, except that the TAE / Mg content in the internal aqueous phase solution is different. 2+ The concentration of the buffer system is 0.1×. During the gradient concentration process, the concentration of the external phase salt solution is successively higher than that of the internal aqueous phase solution (TAE / Mg). 2+ The buffer system concentrations were 10, 30, 50, and 80 times, with a liquid exchange interval of 1 day for each concentration.
[0073] like Figure 8 As shown in Figure A, microscopic observation reveals that the obtained microspheres exist as independent microspheres, and corresponding DNA crystal structures can be observed inside the microspheres. This example illustrates that at a lower internal aqueous phase TAE / Mg... 2+ Under buffer system concentration conditions, single-sphere, single-crystal DNA microspheres can still be constructed by mild concentration in the first stage followed by a gradual increase in the concentration of the outer phase salt solution.
[0074] Example 5 The preparation method is the same as in Example 2, except that the TAE / Mg content in the internal aqueous phase solution is different. 2+ The concentration of the buffer system is 0.5×. During the gradient concentration process, the concentrations of the external phase salt solution are sequentially the same as those of the internal aqueous phase solution (TAE / Mg). 2+ The buffer system concentrations were 10, 30, 60, and 90 times, with a liquid exchange interval of 1 day for each concentration.
[0075] like Figure 8 As shown in Figure B, microscopic observation reveals that the obtained microspheres exist as independent microspheres, and corresponding DNA crystal structures can be observed inside the microspheres. This example illustrates that at a higher internal aqueous phase TAE / Mg... 2+ Under buffer system concentration conditions, by controlling the concentration of the external phase salt solution in the first stage and ensuring that the concentration of the external phase salt solution in the final stage reaches the TAE / Mg ratio in the internal aqueous phase solution... 2+ Even at 70 to 90 times the concentration of the buffer system, single-sphere, single-crystal DNA microspheres can still be obtained.
[0076] Example 6 The preparation method is the same as in Example 2, except that the TAE / Mg content in the internal aqueous phase solution is different. 2+ The concentration of the buffer system is 0.2×. During the gradient concentration process, the concentration of the external phase salt solution is successively higher than that of the internal aqueous phase solution (TAE / Mg). 2+The buffer system concentrations were 5, 20, 50, and 80 times, with a liquid exchange interval of 1 day for each concentration.
[0077] like Figure 8 As shown in C, microscopic observation reveals that the obtained microspheres exist as independent microspheres, and the corresponding DNA crystal structure can be observed inside the microspheres. This example illustrates that the concentration of the outer phase salt solution in the first stage can be the same as the TAE / Mg concentration in the inner aqueous phase solution. 2+ The concentration of the buffer system is 5 times that of the buffer system, and DNA crystal formation and microsphere solidification can be achieved by gradually increasing the concentration of the outer phase salt solution.
[0078] Comparative Example 1 The preparation method is the same as in Example 1, except that HAMA is not added to the aqueous phase solution.
[0079] The dual emulsion droplets were constructed and gradient concentrated using the same method as in Example 1. The results are as follows: Figure 9 As shown, under these conditions, although DNA crystal formation can be observed within the droplet, the resulting crystals are mostly fragmented, polycrystalline, or irregularly aggregated, making it difficult to obtain a single-crystal structure with a relatively regular morphology. Further degreasing and elution did not yield any independent microspheres with stable boundaries.
[0080] Compared to Example 1, a more regularly shaped single-crystal structure was observed in the HAMA-containing system, while in the HAMA-free system, although crystals could form, the single-crystal formation effect was poor, and independent microsphere entities could not be formed during subsequent degreasing and rinsing processes. These results indicate that under the conditions of this embodiment, HAMA can not only serve as a matrix precursor for subsequent microsphere formation but also facilitate the acquisition of single-crystal structures within droplets.
[0081] Comparative Example 2 The preparation method is the same as in Example 1, except that in step (3), no solidification treatment is performed. Instead, the oil phase is removed by direct filtration and then cleaned with 2M NaCl aqueous solution.
[0082] The results are as follows Figure 10 As shown, without the curing step, a microsphere structure with intact boundaries was not obtained; only a polymer phase with a certain degree of aggregation could be observed. Meanwhile, the original crystal structure within the droplet did not exhibit the same intact microsphere encapsulation morphology as in Example 1 after subsequent processing.
[0083] The results show that, under the conditions of this implementation, the presence of polymer alone is insufficient to form a stable microsphere entity. A curing step is also required to form a continuous network of polymer within the droplet, thereby maintaining the independent microsphere structure after degreasing and washing, and retaining the crystals formed within the droplet inside the microsphere.
[0084] Comparative Example 3 The preparation method is the same as in Example 1, except that in step (2), a gradient concentration is not performed, but the two emulsions are placed in the final hyperosmolar external phase for direct concentration in one step.
[0085] The crystal state within the directly concentrated droplet is as follows Figure 11 As shown, microscopic observation reveals that the crystal size distribution of the gradient concentration group is relatively more concentrated and the outline is relatively more regular, while the direct concentration group is more likely to exhibit polycrystalline structures or crystal clusters.
[0086] These results demonstrate that, under polymer-involved conditions, the concentration method significantly impacts the crystal formation process within droplets. Compared to direct concentration, gradient concentration is more conducive to obtaining single-crystal structures and subsequent formation of single-sphere microspheres.
[0087] Microsphere stability analysis The single-sphere single-crystal DNA crystal microspheres containing Alexa Fluor 488-labeled DNA crystals obtained in Example 2 were degreased and washed, then aliquoted into different storage containers and stored under the following conditions: 4°C, 37°C, 50°C, approximately 10% relative humidity, and approximately 75% relative humidity. The approximately 10% relative humidity condition was maintained by anhydrous calcium chloride, and the approximately 75% relative humidity condition was maintained by a saturated sodium chloride solution. The storage time was 20 days.
[0088] After storage, samples from each group were removed, and the morphology of the microspheres, the outline of the DNA crystals inside the microspheres, and the Alexa Fluor 488 fluorescence signal were observed using bright-field microscopy and fluorescence microscopy. Results are as follows: Figure 12 As shown, after storage at 4℃, 37℃, 50℃, and different humidity levels for 20 days, fluorescence signals corresponding to the DNA crystal positions within the microspheres were still observed in multiple sample groups, and the crystal outlines remained identifiable. Under dry or low-temperature conditions, the overall morphology of the microspheres and the internal crystal signals were well preserved. These results indicate that fluorescently labeled DNA crystals, after being embedded and solidified in a hydrophilic polymer microsphere matrix, exhibit good structural retention and fluorescence traceability under different storage conditions. Compared to DNA crystals without microsphere solidification or droplet-like DNA crystals, the DNA crystal microspheres obtained in this embodiment more easily maintain their independent microsphere morphology and internal crystal signals during storage, transfer, and subsequent microscopic observation, demonstrating that the method of this invention can improve the operational and storage stability of DNA crystals.
[0089] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A single-sphere, single-crystal DNA crystal microsphere, characterized in that, It includes a cross-linked network microsphere matrix formed by curing a cross-linkable hydrophilic polymer, and a DNA crystal located inside and surrounded by the cross-linked network microsphere matrix, wherein each microsphere contains only one DNA crystal, forming a single-sphere single-crystal structure; The single-sphere, single-crystal DNA crystal microspheres were prepared by the following method: (1) Prepare an inner aqueous phase solution by mixing DNA strands, crosslinkable hydrophilic polymers, photoinitiators, buffer solutions, surfactants and soluble salts, prepare an intermediate oil phase solution by mixing non-water-soluble substances and non-water-soluble organic solvents, and prepare an outer aqueous phase solution by mixing surfactants. (2) The inner aqueous phase solution, oil phase solution and outer aqueous phase solution obtained in step (1) are respectively introduced into the corresponding channels of the microfluidic chip to prepare a double emulsion droplet loaded with DNA strand; (3) Subsequently, the double emulsion was dropped into an external salt solution with gradually increasing salt concentration for gradient concentration, inducing DNA strands to self-assemble in situ in the internal aqueous environment to form a single DNA crystal. (4) After the DNA crystal is formed, the double emulsion droplets are solidified to form a cross-linked network surrounding the DNA crystal. The oil phase is removed and the microspheres are cleaned to obtain single-crystal DNA crystal microspheres.
2. The single-sphere single-crystal DNA crystal microsphere according to claim 1, characterized in that, The crosslinkable hydrophilic polymer is an anionic hydrophilic polymer containing photocrosslinkable unsaturated groups.
3. The single-sphere single-crystal DNA crystal microsphere according to claim 2, characterized in that, The crosslinkable hydrophilic polymer is selected from at least one of methacrylamide hyaluronic acid, methacrylamide sodium alginate, and methacrylamide carboxymethyl cellulose.
4. The single-sphere single-crystal DNA crystal microsphere according to claim 1, characterized in that, The DNA crystal is formed by the self-assembly of DNA chains, wherein the DNA chains are a combination of central chain (L chain), side chain (M chain), and corner chain (S chain) or a self-assembled chain (Z chain).
5. The single-sphere single-crystal DNA crystal microsphere according to claim 4, characterized in that, The DNA strands described are a central strand (L strand) with the nucleotide sequence SEQ ID NO.1, a side strand (M strand) with the nucleotide sequence SEQ ID NO.2, and a corner strand (S strand) with the nucleotide sequence SEQ ID NO.
3.
6. The single-sphere single-crystal DNA crystal microsphere according to claim 1, characterized in that, The microspheres have a particle size of 10~100μm, and the DNA crystals have a maximum lateral dimension of 1~30 μm.
7. The single-sphere single-crystal DNA crystal microsphere according to claim 1, characterized in that, In step (1), the DNA chain is a combination of a central L chain, a side M chain, and a corner S chain. In the aqueous solution, the concentration of the central L chain is 2~20 μM. The molar ratio of the L chain, M chain, and S chain is 1:3:
3.
8. The single-sphere single-crystal DNA crystal microsphere according to claim 1, characterized in that, In step (1), the internal aqueous phase solution contains TAE / Mg 2+ The buffer system, the TAE / Mg 2+ The concentration of the buffer system is 0.1×~5×.
9. The single-sphere single-crystal DNA crystal microsphere according to claim 1, characterized in that, In step (2), before gradient concentration, the core droplet diameter of the initial dual emulsion droplet is 80~300 μm, and the core droplet diameter of the dual emulsion droplet after gradient concentration is 10~80 μm.
10. The single-sphere single-crystal DNA crystal microsphere according to claim 1, characterized in that, The photoinitiator is 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylphenylacetone, and the curing treatment is curing under 365 nm light for 10-30 min.
11. The single-sphere single-crystal DNA crystal microsphere according to claim 1, characterized in that, In step (3), the gradient concentration involves placing the two emulsion droplets sequentially into two or more external phase salt solutions with gradually increasing salt concentrations, causing the core droplets of the two emulsion droplets to dehydrate and shrink step by step until the diameter of the core droplets of the two emulsion droplets shrinks to 10~80 μm and DNA crystals are formed inside the droplets.
12. The single-sphere single-crystal DNA crystal microsphere according to claim 11, characterized in that, The gradient concentration includes a first-stage concentration, wherein the concentration of the external phase salt solution used in the first-stage concentration is equal to the TAE / Mg concentration in the internal aqueous phase solution. 2+ The concentration of the buffer system is 5 to 30 times that of the buffer system.
13. The single-sphere single-crystal DNA crystal microsphere according to claim 12, characterized in that, Following the first stage of concentration, gradient concentration is further carried out using an external phase salt solution with progressively increasing concentration, and the final concentration of the external phase salt solution is equal to the TAE / Mg concentration in the internal aqueous phase solution. 2+ 70 to 90 times the concentration of the buffer system.
14. The use of the single-sphere single-crystal DNA crystal microspheres according to any one of claims 1 to 13 in the preparation of carriers for nucleic acid coding, molecular tagging, or information storage.
Citation Information
Patent Citations
Soluble hydrogel microspheres, their preparation methods, and their application in single-cell detection
CN109851711B
DNA sequencing using hydrogel beads
CN111094589A
Incubation method of self-assembled organic material crystal based on double emulsion droplets
CN119980475A
Stabilized protein crystals, formulations comprising them and methods of making them
US8558048B2
Nucleic acid microspheres, production and delivery thereof
US9339465B2